"When we were young, it really was a treat; now sugar is just the norm every day"—A qualitative study of parents' and young adults' perceptions and consumption of sugary drinks. (29th May 2019) - Miller, Caroline; Braunack‐Mayer, Annette; Wakefield, Melanie; Roder, David; O'Dea, Kerin; Dono, Joanne; Ettridge, Kerry
Abstract: Issue addressed: Sugar‐sweetened beverages (SSB) are the leading source of free sugars in Australian children's and adults' diets. This study explores drivers of consumption among parents and young adults to inform interventions. Methods: Eight focus groups (n = 59) stratified by gender, age/life stage and SES were analysed thematically. Results: Daily SSB consumption was normalised. Participants drank SSBs to avoid perceived energy/sugar deficits, to treat themselves and as a function of familial influence. Frequent consumption was considered acceptable if "in moderation" and/or "balanced" with exercise/diet; however, there was a large disconnect between this language of moderation and actual consumption practices. Participants acknowledged that social norms had changed over time. There was little evidence of accurate knowledge of sugar content for any beverage type. Participants relied heavily on packaging and labelling, much of which conveyed a health halo effect. While participants could list health effects of excess consumption, they were considered long‐term or of low personal relevance. Awareness of health recommendations was low. Conclusions: Consumers' adoption and use of concepts such as "treat, " "moderation" and "balance" reflect both food and beverage industry marketing and public health messaging. However, the disconnect between this language and knowledge and consumption practices is problematic. So what?: SSB consumption is very high with serious implications for health. Curbing consumption among young adults and parents has potential to change the health trajectories for current and future generations. There is a clear need to increase health literacy around SSB consumption. Simple consumption guidelines, clearer sugar content labelling and health warnings offer potential.